Incredulity towards global-warming crisis: ecocriticism in Ian McEwan’s Solar - Habibi, Seyed Javad; Karbalaei, Sara Soleimani (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2015)
Incredulity towards the metanarrative emerged from discourses conducted during various international summits on global warming is one of the themes that can be underlined in the light of ecocriticism in Ian McEwan’s Solar. Considering one of the most common interactions between nature and culture and assuming a parallelism between natural and artificial photosynthesises, this enquiry attempts to demonstrate that imitating nature might have been one of the techniques suggested satirically in Solar for overcoming this global disaster if science had been at the service of humanity and scientists had not been so egotistical. This study exposes how these money-minded scientists and their sciences do not let these universal congregations become practical and efficient for a world caught in global warming predicament.